Preventive chemotherapy reverses covert, lymphatic‐associated tissue change in young people with lymphatic filariasis in Myanmar. Issue 4 (7th March 2019) - Douglass, Janet; Dykes, Lukah; Kelly‐Hope, Louise; Gordon, Susan; Leggat, Peter; Aye, Ni Ni; Win, San San; Wai, Tint; Win, Yi Yi; Nwe, Thet Wai; Graves, Patricia
Abstract: Objectives: This longitudinal comparative study investigated the effect of preventive chemotherapy (PC) on covert tissue changes associated with lymphatic filariasis (LF) among young people living in an LF‐endemic area in Myanmar. Methods: Tissue compressibility and extracellular free fluid in the lower limbs of people aged 10–21 years were measured using indurometry and bioimpedance spectroscopy (BIS). Baseline measures were taken in October 2014, annual mass drug administration (MDA) of PC was delivered in December, and in March 2015 further PC was offered to LF‐positive cases who had missed MDA. Follow‐up measures were taken in February and June 2015. Results: A total of 50 antigen‐positive cases and 46 antigen‐negative controls were included. Self‐reported PC consumption was 60.1% during 2014 MDA and 66.2% overall. At second follow‐up, 24 of 34 cases and 27 of 43 controls had consumed PC. Significant and clinically relevant between‐group differences at baseline were not found post‐PC. Bayesian linear mixed models showed a significant change in indurometer scores at both calves for antigen‐positive cases who consumed any PC (dominant calf: −0.30 [95% CI −0.52, −0.07], P < 0.05 and non‐dominant calf: −0.35 [95% CI −0.58, −0.12], P < 0.01). Changes in antigen‐negative participants or those not consuming PC were not significant. Conclusion: This study is the first attempt to use simple field‐friendly tools to track fluid and tissue changes after treatment of asymptomatic people infected with LF. Results suggested that PC alone is sufficient to reverse covert lymphatic disturbance. Longer follow‐up of larger cohorts is required to confirm these improvements and whether they persist over time. These findings should prompt increased efforts to overcome low PC coverage, which misses many infected young people, particularly males, who are unaware of their infection status, unmotivated to take PC and at risk of developing lymphoedema. Indurometry and BIS should be considered in assessment of lymphatic filariasis‐related lymphedema. Abstract : Objectifs: Cette étude comparative longitudinale a investigué l'effet de la chimiothérapie préventive (CP) sur les modifications tissulaires cachées associées à la filariose lymphatique (FL) chez les jeunes vivant dans une zone d'endémie pour la FL au Myanmar. Méthodes: La compressibilité des tissus et le liquide libre extracellulaire dans les membres inférieurs des personnes âgées de 10 à 21 ans ont été mesurés par indurométrie et spectroscopie de bioimpédance (BIS). Les mesures de base ont été prises en octobre 2014, la distribution en masse de médicament (DMM) annuelle a été administrée en décembre et en mars 2015, et une CP additionnelle a été offerte aux cas positifs pour la FL qui avaient manqué la DMM. Des mesures de suivi ont été prises en février et juin 2015. Résultats: 50 cas positifs pour l'antigène et 46 témoins négatifs ont été inclus. L'administration de CP auto‐déclarée était de 60, 1% durant la DMM de 2014 et de 66, 2% au total. Au deuxième suivi, 24 des 34 cas et 27 des 43 témoins avaient pris la CP. Des différences significatives et cliniquement pertinentes entre les groupes au départ n'ont pas été trouvées après la CP. Les modèles mixtes linéaires bayésiens ont montré un changement significatif des scores d'indurometrie aux deux mollets pour les cas positifs pour l'antigène qui prenaient une CP (mollet dominant: ‐0, 30 [IC95%: ‐0, 52, ‐0, 07], p <0, 05, mollet non dominant: ‐ 0, 35 [IC95%: ‐0, 58, ‐0, 12], p <0, 01). Les changements chez les participants négatifs pour l'antigène ou ceux qui ne prenaient pas de CP n'étaient pas significatifs. Conclusion: Cette étude est la première tentative d'utilisation d'outils simples, conviviaux sur le terrain, pour suivre les modifications du tissu conjonctif après le traitement de personnes asymptomatiques infectées par la FL. Les résultats suggèrent que la CP seule est suffisante pour inverser les modifications lymphatiques cachées. Un suivi plus long de plus grandes cohortes est nécessaire pour confirmer ces améliorations et déterminer si elles persistent ou non. Ces résultats devraient inciter à redoubler d'efforts pour surmonter la faible couverture en CP, qui rate beaucoup de jeunes infectés, en particulier les hommes, qui ne sont pas au courant de leur statut d'infection, qui ne sont pas motivés pour prendre une CP et risquent de développer un lymphœdème. L'indurométrie et la BIS devraient être considérées dans l'évaluation du lymphoedème associé à la filariose lymphatique.